The ROLE OF FINANCIAL BEHAVIOR IN MEDIATION THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL SELF EFFICACY ON FINANCIAL WILL BEING - Bangun, Bangun Putra Prasetya; Nany Noor Kurniyati (International Journal of Economics and Management Research, 2022)
The purpose of this study is to review the factors that influence Financial Well Being including Financial Literacy, Financial Self Efficacy, Financial Behavior. This study uses SEM data analysis with a sample of 99. Based on the results of data processing, it shows that Financial Self Efficacy on Financial Behavior, Financial Self Efficacy on Financial Will Being and Financial Behavior on Financial Will Being. Meanwhile, Financial Literacy is stated to have no significant effect on Financial Behavior. and Financial Literacy has no significant effect on Financial Will Being. Related to mediation shows that financial behavior cannot mediate Financial Literacy and financial self-efficacy towards Financial Will Being